A web based analysis and scenario tool for eutrophication of inland waters for Sweden and Europe. (January 2019) - Strömbäck, Lena; Pers, Charlotta; Strömqvist, Johan; Lindström, Göran; Gustavsson, Jens
Abstract: Eutrophication of inland water is a serious problem in large parts of the world. Mitigation actions for improved water status are important but often costly to implement. Therefore, tools for estimating the plausible effect of mitigation scenarios are needed to plan which actions are most effective. In this paper we implement a web based interactive tool that allows quick exploration of several alternative mitigation scenarios. In the paper we motivate and describe the method of deriving the tool from more complex modelling systems. We implement tools for Sweden and Europe based on the hydrological simulation models S-HYPE and E-HYPE. S-HYPE is used as one important source of information for Sweden's reporting of water status within the European Union Water Framework Directive. We evaluate the approach by showing that hypothetical changes in load and realistic scenarios have good agreement with full model simulation. Highlights: A tool that instantaneously shows the effect of nutrient reduction scenarios. The results are comparable to more advanced simulations for realistic measures. Two versions of the tool for Sweden and Europe are openly available on internet.